(untitled) (Bangladesh Medical Journal, 2020)
Pre-eclampsia induced liver disease is a disorder unique to pregnancy and is frequently seen in third trimester. Severe pre-eclampsia is defined by extreme elevation in systemic blood pressure and evidence of organ compromise. HELLP syndrome is a unique liver related disorder of pregnancy that was first described by Weinstein in1982 as a constellation of clinical and laboratory abnormalities in pregnant women in their third trimester. This disorder was termed HELLP syndrome with (H) for haemolysis, (EL) for elevated liver enzymes and (LP) for low platelet counts. This is a severe variant of pre-eclampsia. Objective of this study was to determine the alteration of liver function in preeclampsia and its correlation with the clinical severity as well as the perinatal outcome. This was a one-year prospective observational cross sectional study included 100 patients with pre-eclampsia. Severity of the pre-eclampsia clarified clinically. Pre-eclampsia patients having history of hepatitis, cirrhosis of liver, gallbladder diseases and other pre-existing medical disorders that altered liver function were excluded from this study. The mean age of the patients was 25.3+4.9 years ranging from 18 to 37 years. One third of the patients (33.3%) were in the age group 28 to 32 years. Out of 100 patients, 58% belongs to poor income group. Among the studied samples 17% had epigastric pain and discomfort, 13% had complaints of vomiting and 43% develop severe pre-eclampsia. Among the Patients with altered hepatic enzyme level, 8.33% had complaints of epigastric pain, 6.66% complains vomiting. Maximum patients (66.6%) with elevated liver enzyme had no major complications whereas 33.4% of patients developed major complications. Patients with severe pre-eclampsia have elevated liver enzyme whereas patients of mild symptoms had normal liver enzymes level. Cases with raised serum biochemical markers had strong association with complications of severe pre-eclampsia. Pregnancy outcome in severe pre-eclampsia with hepatic involvement is grievous. Graves sequlae of pre-eclampsia can be prevented and minimized by timely institutional intervention. Post-partum followup would help to find out other parameters of pregnancy outcome. Bangladesh Med J. 2020 May; 49(2) : 9-13